2018
DOI: 10.1115/1.4041864
|View full text |Cite
|
Sign up to set email alerts
|

Studying a Hybrid System Based on Solid Oxide Fuel Cell Combined With an Air Source Heat Pump and With a Novel Heat Recovery

Abstract: In this paper, a new heat recovery for a microcogeneration system based on solid oxide fuel cell and air source heat pump (HP) is presented with the main goal of improving efficiency on energy conversion for a residential building. The novelty of the research work is that exhaust gases after the fuel cell are first used to heat water for heating/domestic water and then mixed with the external air to feed the evaporator of the HP with the aim of increasing energy efficiency of the latter. This system configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Building-integrated HRESs with at least two RESs (i.e., solar-wind, solar-geothermal, or solar-biomass) are considered. Vialetto et al [30] demonstrated heat recovery for an air source heat pump system with the main aim of improving energy conversion efficiency for a residential building. The authors' results confirm that the efficiency of the AHP is increased during the cold season in climates with high relative humidity and for users with high power demands.…”
Section: Introductionmentioning
confidence: 99%
“…Building-integrated HRESs with at least two RESs (i.e., solar-wind, solar-geothermal, or solar-biomass) are considered. Vialetto et al [30] demonstrated heat recovery for an air source heat pump system with the main aim of improving energy conversion efficiency for a residential building. The authors' results confirm that the efficiency of the AHP is increased during the cold season in climates with high relative humidity and for users with high power demands.…”
Section: Introductionmentioning
confidence: 99%